Pengaruh Produk Bank Syariah Mandiri Terhadap Minat Menabung Masyarakat Kecamatan Muara Tembesi Kabupaten Batanghari - Sumantri Sumantri (CITRA EKONOMI, 2020)
Interest is a psychological aspect and not just coloring someone's behavior to do activities that cause someone to feel attracted to something. Besides interest has a broad meaning, because with interest will be able to change something that is not clear to be clearer. Interest is an interest or tendency that is closely related to feelings, especially feeling happy (positive) towards something that is considered valuable or as needed and gives satisfaction to it and the products issued by Bank Mandiri Syariah are a group of services produced by Bank Mandiri Syariah which then offered to the community in order to facilitate the community in placing their funds so that the funds owned are safe. The purpose of this journal preparation is to Want to Analyze the influence of Bank Mandiri Syariah Products on the interest of saving people in Muara Tembesi, Batanghari Regency. The research method used in this research is to use quantitative descriptive which is a study using data analysis in the form of numeric or numeric. The purpose of this study is to develop and use mathematical models or theories related to the phenomena investigated by researchers. From the data obtained by the researcher, what is the objective of this in-research study which includes the influence of Bank Mandiri Syariah products on the interest of saving the Muara Tembesi community in Batanghari Regency.